2019
DOI: 10.1111/dmcn.14407
|View full text |Cite
|
Sign up to set email alerts
|

The expanding spectrum of movement disorders in genetic epilepsies

Abstract: An ever‐increasing number of neurogenetic conditions presenting with both epilepsy and atypical movements are now recognized. These disorders within the ‘genetic epilepsy‐dyskinesia’ spectrum are clinically and genetically heterogeneous. Increased clinical awareness is therefore necessary for a rational diagnostic approach. Furthermore, careful interpretation of genetic results is key to establishing the correct diagnosis and initiating disease‐specific management strategies in a timely fashion. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 188 publications
2
34
0
Order By: Relevance
“…Although more than 100 genes have been associated with complex monogenic neurologic disorders featuring pediatric-onset DE/EE and MD [61][62][63], this association has been less investigated in newborns. As a result, the number of reviewed studies is low and, for 70% of genes, only single papers were available.…”
Section: Discussionmentioning
confidence: 99%
“…Although more than 100 genes have been associated with complex monogenic neurologic disorders featuring pediatric-onset DE/EE and MD [61][62][63], this association has been less investigated in newborns. As a result, the number of reviewed studies is low and, for 70% of genes, only single papers were available.…”
Section: Discussionmentioning
confidence: 99%
“…We further found that both male and female Adcy5 –/– mice were characterized by significantly lower voluntary running wheel activity in metabolic chambers. As mutations in the Atp1a3 gene are known to be related to dyskinesia, epilepsies and Parkinson’s disease [ 43 ] this could be a relevant finding in the context of other reports describing a connection between the loss of Adcy5 and movement disorders like dyskinesia or autism-like behavior [ 44 , 45 , 46 ]. Furthermore, we cannot exclude that lower activity in our Adcy5 –/– mice was caused by previously reported movement disorders and contributed to the phenotype differences compared to previous Adcy5 –/– models [ 11 , 13 , 24 ].…”
Section: Discussionmentioning
confidence: 92%
“…Second, genetic heterogeneity is also commonly observed in electroclinical syndromes, when different genes can produce one phenotype. Ohtahara syndrome is an example of genetic heterogeneity with several causative mutated genes already described, including STXBP1, 15 SCN2A, 16 ARX, 17 CASK, 18 GNAO1. 19 When to consider genetic testing Genetic discoveries have enhanced our ability to diagnose developmental and epileptic encephalopathies in clinical practice.…”
Section: Overview Of Epilepsy Geneticsmentioning
confidence: 99%